Preparation, Characterization, and Application of Metakaolin-Based Geopolymer for Removal of Methylene Blue from Aqueous Solution - Marouane El Alouani; Saliha Alehyen; Mohammed El Achouri; M’hamed Taibi (Journal of Chemistry)
Metakaolin-based geopolymers are aluminosilicate materials that can be used as cationic dye adsorbents in aqueous system treatment. Our aim in this paper is to study the ability of geopolymer powder produced from metakaolin and alkaline activators to act as an adsorbent to remove methylene blue (MB). The solid materials were systematically analyzed by X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier-transform infrared spectrometery (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and the point of zero charge. XRF, FTIR, XRD, SEM, and EDX analyses confirmed the formation of a geopolymer composite by geopolymerization reaction. The influence of various experimental factors such as geopolymer dosage, pH, initial dye concentration, contact time, and temperature was assessed. Adsorption isotherms were evaluated by Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherms. Kinetics data were studied using pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. The thermodynamic parameters, namely, Gibbs free energy (ΔG°), enthalpy (ΔH°), and entropy (ΔS°), were determined. The results indicated that the maximum decolorization was found in high pH values. The collected isotherm data were best fitted by the Langmuir isotherm, and the maximum adsorption capacity of dye onto the geopolymer was 43.48 mg/g. The experiment kinetics followed the pseudo-second-order kinetic models. The thermodynamic results demonstrated that the adsorption of the obtained material occurs spontaneously as an endothermic process. The results confirmed that the prepared adsorbent can be used for remediation of water contaminated by MB dye.